Seed morphology diversity in some Iranian endemic Silene (Caryophyllaceae) species and their taxonomic significance - Arman, Mitra; Gholipour, Abbas (Acta Biologica Szegediensis, 2013)
Seed morphology diversity of 16 endemic Silene species was studied using Scanning Electron Microscope (SEM) to describe the seed micromorphology features and evaluate their taxonomic significance. Fifteen qualitative and quantitative characters were measured using SEM micrographs and stereomicroscopy. The seeds shape of the most species is reniform. The size of seeds ranges from 0.85 × 0.62 mm in case of S. elymaitica to 2.28 × 1.4 mm in S. nizvana. The ornamentation of seed coat is papillate in S. elymaitica and S. oligophylla, tuberculate in S. daenesis and the seed surface of the rest is smooth. Three types of the edge of testa cells; V form, U form and entire were observed. This study indicates that seed characters, such as shape, size, dorsal surface, the shape and size of testa cells, the testa cells edge and testa cells surface ornamentation are useful in identification and classification of the species studied. An identification key is also presented based on seed morphology characters.